Exosome-mediated miR-146a transfer suppresses type I interferon response and facilitates EV71 infection. - Yuxuan Fu; Li Zhang; Fang Zhang; Ting Tang; Qi Zhou; Chunhong Feng; Yu Jin; Zhiwei Wu (PLoS Pathogens)
Exosomes can transfer genetic materials between cells. Their roles in viral infections are beginning to be appreciated. Researches have shown that exosomes released from virus-infected cells contain a variety of viral and host cellular factors that are able to modulate recipient's cellular response and result in productive infection of the recipient host. Here, we showed that EV71 infection resulted in upregulated exosome secretion and differential packaging of the viral genomic RNA and miR-146a into exosomes. We provided evidence showing that miR-146a was preferentially enriched in exosomes while the viral RNA was not in infected cells. Moreover, the exosomes contained replication-competent EV71 RNA in complex with miR-146a, Ago2, and GW182 and could mediate EV71 transmission independent of virus-specific receptor. The exosomal viral RNA could be transferred to and replicate in a new target cell while the exosomal miR-146a suppressed type I interferon response in the target cell, thus facilitating the viral replication. Additionally, we found that the IFN-stimulated gene factors (ISGs), BST-2/tetherin, were involved in regulating EV71-induced upregulation of exosome secretion. Importantly, in vivo study showed that exosomal viral RNA exhibited differential tissue accumulation as compared to the free virus particles. Together, our findings provide evidence that exosomes secreted by EV71-infected cells selectively packaged high level miR-146a that can be functionally transferred to and facilitate exosomal EV71 RNA to replicate in the recipient cells by suppressing type I interferon response.